The impact of local loop and retail unbundling - Gordon J. Klein; Julia Wendel (International Telecommunications Society (ITS), 2014)
For more than a decade the unbundling of telecommunications networks has been used as a regulatory means to stifle competition. However, despite its assumed positive effects on market entry and competition intensity, the negative effects on network investment incentives are widely shown in the theoretical literature. Therefore broadband penetration might also be affected negatively. In our paper we concentrate on the impact of local loop unbundling and Bitstream access on broadband penetration. Using a panel of European countries for a time period of 17 years, we find that the effect of unbundling on penetration is positive when an intermediate level of broadband penetration has been achieved in a country. However, this impact turns negative if the initial level of broadband penetration is rather low or high. We argue that this confirms possible negative effects on investment incentives, but may successfully lower prices to foster demand. These are two findings which should be carefully considered by policy makers when deciding on unbundling policies.
Keywords: 330; Broadband Internet Penetration; Local Loop Unbundling; Bitstream Access; Policy Evaluation; Panel Data Analysis